Policy Assessment of Wheat Production in Turkey - Nazli Ceylan (Zeszyty Naukowe Szkoły Głównej Gospodarstwa Wiejskiego w Warszawie. Problemy Rolnictwa Światowego)
Turkey plays a significant role in global wheat trade, importing wheat grain and exporting processed wheat products such as pasta, flour and biscuits. Wheat growing areas in Turkey have shown a decrease of about 10% over the last decade. Although an increase in yields keeps the production amount in balance, policies toward the wheat sector have reached a more critical point due to an increasing population and growing demand on the wheat flour sector. In this study, the profitability and sustainability of the sector were analyzed by using the Policy Analysis Matrix (PAM) approach, and by examining the effects of the policies that have been applied on the wheat market recently. According to the PAM results, domestic wheat prices are higher than world prices due to existing policies and the wheat sector is not competitive without support.